M13 bacteriophage/single-walled carbon nanotube interactions for chirality selection and multifunctional materials - Yu, Ting (2012)
Filamentous M13 bacteriophages are excellent display systems and nanoscale building blocks. Single-walled carbon nanotubes (SWCNTs) have promising prospects in a wide range of applications, from molecular electronics to artificial muscles, owing to their fascinating electronic and mechanical properties. The interaction between these two novel materials was studied and exploited in this dissertation. In the first part of this thesis, phage display screening was performed for SWCNT chirality separation. Structural similarities of (7, 5) and (7, 6) binding peptides were found, such as high contents of aromatic amino acids, histidine as the head of peptides, and overall hydrophobicity, etc. The SWCNT-peptide interaction was further studied by molecular dynamics (MD) simulations to reveal the binding conformation and to calculate the binding energy. Peptide HSNWRVPSPWQL, which was selected by phage display screening and MD simulations, was able to disperse SWCNTs into small bundle and individual tubes and to preferentially disperse large-diameter SWCNTs. In the second part, M13 phages, as nanoscale building blocks, were fabricated into centimeter-long liquid-crystalline microfibers with inherent fluorescence by crosslinking reaction. SWCNTs and magnetic nanoparticles were added into the fibers as functional fillers. The multifunctional phage composite fibers, integrating fluorescence, electrical conductivity, magnetism, improved mechanical properties, biocompatibility, and surface functionalization sites, are promising all-in-one tools for carrying out different tasks in parallel.